Gendered vocational identities: Female students' strategies for identity formation during workplace-based learning in male-dominated work - Lisa Ferm; Maria Gustavsson (International Journal for Research in Vocational Education and Training (IJRVET), 2021)
Purpose: This article investigates female vocational students' strategies for becoming part of a workplace community, what these strategies are and how they are tied to the formation of vocational identities within male-dominated industrial work. Of particular interest is how female students enrolled on Swedish upper secondary industrial programmes experience workplace-based learning at industrial workplaces as part of their vocational education. The theoretical framework derives from Wenger's concept of community of practice, but his theoretical concept does not explicitly include gender dimensions. Therefore, the concept of community of practice is also combined with Paechter's assumption of gender, whereby femininity and masculinity can be considered as different communities of practice. Methods: The article draws on evidence from a Swedish study based on interviews with 20 female students enrolled on the industrial programme at six upper secondary schools. In this vocational programme, there is a distinct gender distribution and only a small minority of the students on the programme are girls. In the analysis, the focus is on the female students' strategies used during workplace-based learning to become part of the work community which consists almost exclusively of male workers. Findings: The female students deliberately negotiated vocational identities as female industrial workers to become accepted in the male-dominated work community. The findings highlight three specific strategies that the female students used: Acting like gender does not matter, acting like boys (not like drama queens), and acting tough and joking around. The female students' strategies were part of - and tied to - a complex vocational identity formation process that featured contradictory requirements. By taking individual responsibility, they identified relevant information for becoming industrial workers and chose to act like boys. The female students saw no problem with being a girl, yet they struggled with implicit, diffuse and hidden gender structures and prejudices in the male-dominated industrial companies. Nevertheless, they strived for what they perceived to be an attractive vocational identity as industrial workers; it was an alternative, atypically feminine way of being that attracted the female students. Conclusions: The study concludes that female students mostly rely on their individual agency when interacting with others in the male-dominated workplace community. A "gendered vocational identity" is formed which shows that the identity formation of female students is a complex double process, in which vocational and gender identities are formed simultaneously and in parallel within the male-dominated workplace.
Keywords: 330; VET; Vocational Education and Training; Vocational Identity Formation; Gender; Student; Workplace-based Learning